FARMERâS TRAINING CENTRE AND ITS CONTRIBUTION TO SUCCEED INDONESIAN OVOP (ONE VILLAGE-ONE PRODUCT) IN ATTAINING HOUSEHOLD FOOD SECURITY - Junissa I. S., Dea Christina (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: Farmerâs Training Centre and Its Contribution to Succeed Indonesian OVOP (One Village-One Product) In Attaining Household Food Security. Government has a program, OVOP (one villageâone product) can encourages local communities to develop their village with emphasize on optimizing their potential resources and to utilize this globalization. This paper will discover what the Ministry of Agriculture contribution for succeeding this program is. Talking about the relationship between FTC (the agent of the MoA extension) and OVOP, it has been recognized that each FTC has its specialization. In the other word, FTC is a supporting infrastructure of the OVOP implementation. However it must be evaluated because of some endogenous problems. Here, it will be deeply discussed through the primary data. The benefit of this research is the recommendations for government how to support OVOP movement through FTC. Â  Key words: food security, OVOP and FTC Â  Abstrak: Pusat Pelatihan Petani dan Kontribusi Sukses OVOP Indonesia (One Village One Product-) Dalam Mencapai Ketahanan Pangan Rumah Tangga. Pemerintah membuat suatu program yang dinamakan OVOP (satu desa satu produk) yang dapat mendorong ekonomi daerah dengan memanfaatkan proses globalisasi. Di paper ini akan dibahas lebih jauh mengenai bentuk dukungan pemerintah untuk program ini, khususnya Kementerian Pertanian (Kementan), dikarenakan produk OVOP lebih banyak produk pangan. Untuk mendorong program ini, Kementan bekerjasama dengan P4S yang dianggap dapat menjadi starter atau faktor pendukung utama dalam pelaksanaan OVOP di pedesaan. Penelitian ini dilakukan untuk melihat sejauh mana efektivitas kinerja lembaga ini untuk mendukung program tersebut dan meningkatkan perekonomian anggotanya. Â  Kata kunci: ketahanan pangan, OVOP dan P4S